U.S. Foreign Policy and Religion During the Cold War and the War on Terror Study of How Harry S. Truman and George W. Bush Administrations Procured Public Support for Warfare. - Stramer, Janicke (Lewiston : Edwin Mellen Press, 2011)
Janicke Stramer's book examines the use of religious rhetoric and faith as a tool to garner support for U.S. foreign policy. Stramer's history provides case studies of the Truman administration and the George W. Bush (43) administration. In particular, Stramer examines Truman's use of religion to develop his containment policy against "godless" communism during the Cold War and uses it as a backdrop for an analysis of how religion was applied to the Bush administration's "War on Terror." Using these two studies, Stramer asserts that a framework can be developed to analyze the U.S. perception o
Description based upon print version of record.
Description based on print version record.
Keywords: Bush, George W. -- 1946- -- Ethics; Truthfulness and falsehood -- Political aspects -- United States -- Case studies; United States -- Politics and government -- 2001-2009 -- Sources; United States -- Politics and government -- 2001-2009.; POLITICAL SCIENCE / Government / International; POLITICAL SCIENCE / International Relations / General; HISTORY / United States / 21st Century; Electronic books